PROSPEKTUS REKSADANA SEBAGAI PRINSIP KEJUJURAN BISNIS SYARIAH - Kuat Ismanto (Jurnal Hukum Islam, 2012)
This article aims to discuss about mutual funds, both in conventional and Islamic banks, which have become the choice of investment for the community. It is not remarkable for some prospective investors do not understand about the mutual funds that will be purchased. One way that can be done to find the product is to read the prospectus issued by the company. Prospectus as preliminary information of products (mutual funds) is seen as good will of the company to explain the products that will be sold. From the sharia contract perspective, it is way to eliminate an uncertain or ambiguous subject matter (gharar). Therefore, this article is intended to serve transaction which in accordance with sharia principles.